Housing and Children’s Development and Wellbeing: Evidence from Australian Data - Dockery, Alfred Michael; Ong, Rachel; Colquhoun, S.; Li, Jianghong; Kendall, Garth (Australian Housing and Urban Research Institute, 2013)
This study involved undertaking quantitative analysis of a range of established longitudinal data sets, primarily from the Longitudinal Survey of Australian Children (LSAC). The research findings are consistent with a large overseas literature that has found associations between housing circumstances and a range of child outcomes. The key finding of the analysis is that there are highly statistically significant relationships between a range of aspects of young children’s housing and their outcomes. In terms of their magnitude, however, the effect of housing variables appears to be quite modest. The available housing variables explain very little of the variation in child outcomes beyond what can already be accounted for by a relatively small set of variables capturing background family socio-demographic characteristics.These associations do not necessarily imply causal effects running from housing to children’s outcomes. However, they do appear to be factors that operate in addition to families’ socio-economic status. The factors shaping outcomes vary across different domains of development and wellbeing: In terms of children’s physical health, housing plays a small role in shaping outcomes. This may be due to the reasonably high general level of housing enjoyed by Australian children. Nevertheless, living on a farm and in more livable neighbourhood conditions contribute to better physical health. For children’s social and emotional outcomes, the family aspects of a home are of greater relative importance than physical properties of the buildings. Parenting styles have a much stronger impact than housing variables, while among housing variables it is the things likely to impact upon the quality of relationships—frequent moves, renting rather than owning and being in financial stress—that appear to impact upon children’s social and emotional wellbeing.For children’s learning outcomes, crowding has the largest negative impact. The study suggests that neighbourhood effects are more important than characteristics of individual dwellings in promoting the wellbeing of children, particularly once they pass toddlerhood. Urban planning that features parks, playgrounds and other open areas are likely to be conducive to children’s development and wellbeing even if achieved at the expense of higher density of the actual dwellings. This may have relevance in particular to amenities for families receiving housing assistance, including public housing residents. Two key groups stand out for whom their children’s outcomes are particularly affected by their inferior housing positions: sole parents and Indigenous Australians. There would therefore seem to be a case for closer targeting of existing housing assistance programs for these groups, and the development of forms of assistance that address their particular needs.